Educational path of teachers of Natural Sciences: a bibliographic review, based on Brazilian theses and dissertations - Geovane Barbosa dos Santos; Antônio Azambuja Miragem; Maria Rosa Chitolina (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
The training path and professional practice of Natural Science teachers require multiple knowledge and practices. Paradoxically, the training curriculum (initial or continuing) and working conditions do not help to fulfill these demands. In this sense, the objective is to understand the contributions of dissertations and theses produced in the country, present in the Brazilian Digital Library of Theses and Dissertations (BDTD), on training processes and professional practice of undergraduates and teachers in the area of Natural Sciences. The studies found, based on specific descriptors, underwent inclusion and exclusion criteria. Nineteen documents resulted for the reading and analysis of the full text. It can be seen that the training course of Natural Science teachers presents barriers and challenges that impact their professional practice. However, there are many strategies to minimize them. Therefore, there is a need to look at the educational documentary parameters and relate them to the training path of teachers of Natural Sciences.